KEY FACTORS OF PATHOGENESIS OF CHRONIC PANCREATITIS IN FAMILY DOCTOR’S PRACTICS - Vovk, K.V.; Sokruto, O.V.; Nikolenko, J.Ya.; Savchenko, V.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
During more than one hundred years of researching pathogenesis of chronic pancreatitis (CP) many of the hypothesis have been created. Some of them through time were denied, some were partly confirmed by results of clinical and experimental researchings and became hypothesis. However, not all the elements of pathogenesis of CP are clear till now. Probably, it is caused by large number of etiologic factors in development of CP, part of which have differences in pathogenesis. The hypothesis of 60s-70s of the last century were propounded and refuted exactly without taking into account these differences. The discoveries of the last 15 years, specifically determination of hereditary and autoimmune genesis of CP, have widened a notion of it’s pathogenesis. The majority of scientists consider a pathogenetic significance of the intraductal hypertension and intraductal protein and calcium precipitation. However, in opinion of some researchers, the mechanisms of its’ development are different. The fundamental pathophysiologic hypotheses of CP’s development, many of which are topical today, are considered in this article.